New World gold: cultural anxiety and monetary disorder in early modern Spain - Vilches, Elvira (University of Chicago Press, 2010)
Introduction : money, credit, and value -- New world gold -- Selling the Indies : Columbus and the economy of the marvelous -- Gold : a problematic standard -- The new world of money -- Writing about debt -- The Indies, value, and wealth -- Conclusion : a remote and exotic geography